Student matric card payment system using RFID technology - Alias, Hairi; Azmi, Aida Azmila; Salim, Sufian (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2020)
The Student Matric Card Payment System (SMaCPay) using RFID is an application which utilizes RFID scanner from matric card to record and track the student expenditure at PSMZA cooperative mart. This application is designed specifically to monitor the polytechnic student expenditure record once they purchase at cooperative mart. RFID SMaCPay uses Rapid Application Development (RAD) methodology. The RAD model is an effective methodology to provide much quicker development and higher-quality results than those achieved with the other software development methodologies. It is designed in such a way that, it easily takes the maximum advantages of the software development. This application has been developed using HTML and PHP as it language programming, Javascript as it scripting and MySQL as it database platform. This application enables student to make a payment via RFID tag using their matric card and check the balance amount through the application. Student’s tendency for SMaCPay has been evaluated with min score of 1.61 for technical, 2.02 for user interface, 1.75 for data accuracy and 1.71 for accessibility aspect. Nevertheless, usage of current material for the matric card is quite unsecured due to low quality and result the embedded RFID chip within the card easy to damage which will cause to data loss.